The relationship between cognitive results and psychomotor results of MAN 1 Bandung students in the Jurisprudence Subject Hajj Chapter using the PjBL Learning Model - Muhammad Raja Iqbal Fahri; Jujun Gunawan; Neng Rohaeni; Tarsono Makmuri (Journal of Education Technology Information Social Sciences and Health, 2024)
Technological developments are increasingly rapid, so that the learning process requires educators to be creative and innovative to achieve learning goals. Hajj is one of the Fiqh materials that students must study. Thus, to find out whether there is a relationship between cognitive results and psychomotor results for MAN 1 Bandung students on the Hajj chapter of fiqh material using the PjBL model, research was conducted in class X 2 of MAN 1 Bandung students. The research method uses a correlational quantitative approach, data processing uses a simple linear regression test with the result that the regression coefficient is positive (unidirectional), amounting to 0.679, meaning, if cognitive results increase by 1 unit, then psychomotor results will increase by around 1.679, meaning: if cognitive results increase is 1.679, then the psychomotor results will also increase by 1.679, so there is a relationship between cognitive results and students' psychomotor results using the PjBL learning model.